Vitamin D deficiency and its impact on asthma severity in asthmatic children. Issue 1 (December 2016) - Esfandiar, Nasrin; Alaei, Fariba; Fallah, Shahrzad; Babaie, Delara; Sedghi, Niloofar
Abstract Background Despite obtaining evidences on association between vitamin D and development of lung in fetus, little is known about vitamin D level and its impact on severity of asthma in children. The present study aimed to assess the relationship between the asthma severity and vitamin D deficiency in asthmatic children. Methods This case-control study was conducted on 106 individuals including asthmatic (n  = 53) and healthy children (n  = 53) who referred to Mofid hospital in Tehran in 2013. The level of serum vitamin D in both groups was measured by radioimmunoassay method at the reference lab and was categorized as sufficient (> 30 ng/ml), insufficient (20 to 30 ng/ml), or deficient (< 20 ng/ml). The control status of asthma in patients group was classified as controlled, partially controlled, and uncontrolled. Results In the groups with and without asthma, the prevalence of vitamin D deficiency was 73.6 and 49.1%, and the prevalence of vitamin D insufficiency was 18.9 and 18.9%, while normal vitamin D level was revealed in 7.5 and 32.1%, respectively with a significant difference (p  = 0.005). Using the multivariate logistic regression analysis, the presence of asthma was associated with reduced level of vitamin D (OR = 1.068, 95% CI: 1.027–1.110, P  = 0.001). In this context, the risk for asthma in the children with vitamin D deficiency was 6.3 times of those with normal vitamin D level. Although the presence of asthma was strongly associated with reduced level of vitamin D in serum, neither severity of asthma nor control status of asthma were associated with vitamin D deficiency. Conclusion The presence of vitamin D deficiency effectively predict increased risk for childhood asthma; however the severity or control status of this event may not be predicted by confirming vitamin D deficiency.